Depression, Neuroplasticity and Neurotrophic Factors - Cengiz Akkaya; Salih Saygın Eker; Aslı Sarandöl; Zeynep Kotan (Psikiyatride Güncel Yaklaşımlar, 2009)
Depression is a common psychiatric disorder. There is still very little known about the neurobiological alterations that underlie the pathophysiology of depression. Recently, neuroplasticity hypothesis is added to monoamine hypothesis and neurotransmitter receptor hypothesis which are among the theories about the biological etiology of depression. Neuroplasticity can be defined as alterations in structural properties and functions of neurons and synapses depending on various internal and external stimuli. Neurotrophic factors are molecules important for development and protection of neurons. The neuron needs the neurotrophic factors synthesized by itself for survival, differentiation and neuroplasticity. Hippocampus is one of the brain regions with highest level of neuroplasticity. Brain imaging studies reveal that there is hippocampal volume reduction in depression. This reduction may be due to stress induced alterations in neurogenesis and neurotrophic factor expression in hippocampus. Pharmacologic and somatic antidepressant treatments increase adult hippocampal neurogenesis and neurotrophic factor expression and reverse effects of stress on hippocampal atrophy. Brain derived neurotrophic factor (BDNF) is the mostly studied neurotrophic factor in depression. There are data about decreased levels of BDNF in depression. Many studies suggest that BDNF is the “common final pathway” for actions of different antidepressants and chronic antidepressant treatment can enhance neurogenesis in adult hippocampus regulating plasticity and neurotrophin signalling pathways important in neuronal survival.